DISCLOSING THE TRIGGERS OF FRAUD IN THE MANAGEMENT OF COMMUNITY GROUP GRANT FUNDS (Case Study at Manut Agency of Hilir Province) - Ahmad Syaifullah; Tarjo Tarjo; Siti Musyarofah (Asia Pacific Fraud Journal, 2018)
The purpose of this study is to find out the trigger of fraud in the management of grant funds. This study uses qualitative method with configurative-ideographic case study approach aimed at analyzing the trigger of fraud in the management of community group grant funds more deeply. Data were obtained through interviews with informants consisting of Manut agency, as the manager of society group grant funds, and some grant recipients as well as other parties involved in the management of the grant funds. The result of this study indicates that the trigger of fraud in the management of grant funds is the dominance of access to grant funds by certain parties and the implementation of grant fund management which is not in accordance with the rules that have been set.